PENGAWASAN PANGAN TANPA IZIN EDAR OLEH BALAI BESAR PENGAWAS OBAT DAN MAKANAN DI PEKANBARU DALAM HAL PERLINDUNGAN KONSUMEN - Christin, Jesicha Maria; Ismi, Hayatul; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Not only provide a sense of security to consumers of food products, but also a reference to the quality of production by producers and foods that do not have an unsecured licensing is not safe to consumed by consumers. Based on this matter, the Center for Food and Drug Supervisor should still be able to pay attention to food and food products that must be considered further unsafe food products still. The purpose of this thesis, first, To know the supervision of food without distribution authorization of Food and Drug Supervisory Agency in Pekanbaru in terms of consumer protection. Second, To know the constraints of food control without distribution permit conducted by large hall of drug and food superintendent in Pekanbaru in terms of consumer protection and third, to know the efforts of the barriers in the supervision of food without distribution authorization by large hall of drug and food superintendent in Pekanbaru in terms of consumer protection.In this study the authors use the type of sociological research that is the study of the effectiveness of the prevailing law in society and mengidentifiasi laws that are not written applicable in the community. In this case the author conducted a study on Pekanbaru Food and Drug Supervisory Center regarding the supervision of food without distribution authorization in terms of consumer protection.from the results of this study can be concluded, first, Supervision of food without distribution authorization by the Center for Food and Drug Supervisor in Pekanbaru in terms of consumer protection has been running as it should, but still less than optimal. Second, Barriers in the supervision of food without distribution authorization by large hall of drug and food superintendent in Pekanbaru in terms of consumer protection is due to the limited ability of human resources in the field of supervision and law enforcement and third, Efforts that can be done to overcome barriers of food control without distribution authorization by large hall of drug and food superintendent in terms of consumer protection is by increasingkkam human resources capacity in the field of supervision and law enforcement.Keyword: Food – Consumer – Protection - large hall of drug and food